Innovation and problem solving in bat eared foxes, otocyon megalotis - Jabos, Paul Juan (University of the Free State, 2015)
Cognition, defined as the acquisition, processing, storage and use of information, can have direct fitness consequences, and has emerged as an important subfield within behavioural ecology. Individual differences in cognitive performance have been correlated, inter alia, with relative brain size, the complexity of a species’ social and ecological environment, and personality. Personality refers to stable, long-term behavioural, emotional, and physiological differences in suites of traits among individuals within a species. In order to observe differences in cognitive performance within a species, rates of innovation and problem solving tasks are typically used. Innovation can be operationally defined as ‘a new or modified learned behaviour not previously found in the population’. Problem solving includes decision making allowing animals to overcome obstacles to reach a goal. To date, the majority of studies investigating innovation and problem solving did so by presenting novel problems to isolated captive animals, whose responses may not reflect those seen in natural and social contexts. Moreover, field experiments have primarily been restricted to birds and primates. Tests under natural circumstances are important as they are ecologically and biologically relevant. For example, wild individuals may have divided attention as they need to be vigilant in the presence of predators, compared to captive individuals, for whom predators are not a consideration. The aim of this study was to investigate individual differences in innovation and problem solving in bat-eared foxes (Otocyon megalotis) through observation and an object manipulation task Observations offered an opportunity to witness innovations in the wild. I observed a specific novel foraging event from a female 164 bat-eared fox. This innovation event included the hunting and killing of a hare (Lepus sp.) in order to consume this large prey animal, which was unusual, considering the preferred invertebrate diet of bat-eared foxes, and their dentition specialized for smaller prey. The object manipulation task included manipulating part of a contraption in order to solve a problem and used to determine the influences of personality on learning and problem solving. Foxes were proficient learners in the object manipulation task, where persistence and exploration diversity were important aspects of problem solving. Persistence and exploration behaviour were correlated in the problem solving of bat-eared foxes, providing support for the basis that more explorative and more persistent individuals may be more flexible in solving problems. The effects of high neophobia was only revealed when all trials were considered instead of only the initial trial, thus a higher neophobia may have a long term effect on problem solving ability compared to individuals who are only moderately neophobic. Bat-eared foxes have shown proficient learning abilities and rapidly learned when tasks were presented to them. I show that innovation, problem solving, learning, persistence, neophobia and exploration can influence aspects of animal cognition, further extending our knowledge of animal cognition by using a natural population of bat-eared foxes. These correlates are important for the fitness and survival of bat-eared foxes and their offspring, as foxes can rapidly assess foraging situations (such as extracting termites from a termite mound), opportunistically hunt novel prey and learn new foraging techniques, which can all lead to increased foraging success. I discuss potential future research into bat-eared fox cognition, such as investigating persistence in an unsolvable problem solving task. Unsolvable tasks outside of domestic dog research have been few and are highly encouraged to determine the influence of persistence on problem solving performance. Alternative contexts for the measurement of personality (exploration-avoidance) are also discussed, for example, using an open-field test, which includes monitoring an individual explore a novel space or a known space with novel objects/stimuli in it.
Keywords: Bat-eared fox; Cognitive ecology; Innovation; Personality; Problem solving; Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2015